The Hinge Segment of Human NADPH-Cytochrome P450 Reductase in Conformational Switching: The Critical Role of Ionic Strength - Campelo, Diana; Lautier, Thomas; Urban, Philippe; Esteves, Francisco; Bozonnet, Sophie; Truan, Gilles; Kranendonk, Michel (Frontiers in Pharmacology, 2017)
NADPH-cytochrome P450 reductase (CPR) is a redox partner of microsomal cytochromes P450 and is a prototype of the diflavin reductase family. CPR contains 3 distinct functional domains: a FMN-binding domain (acceptor reduction), a linker (hinge), and a connecting/FAD domain (NADPH oxidation). It has been demonstrated that the mechanism of CPR exhibits an important step in which it switches from a compact, closed conformation (locked state) to an ensemble of open conformations (unlocked state), the latter enabling electron transfer to redox partners. The conformational equilibrium between the locked and unlocked states has been shown to be highly dependent on ionic strength, reinforcing the hypothesis of the presence of critical salt interactions at the interface between the FMN and connecting FAD domains. Here we show that specific residues of the hinge segment are important in the control of the conformational equilibrium of CPR. We constructed six single mutants and two double mutants of the human CPR, targeting residues G240, S243, I245 and R246 of the hinge segment, with the aim of modifying the flexibility or the potential ionic interactions of the hinge segment. We measured the reduction of cytochrome c at various salt concentrations of these 8 mutants, either in the soluble or membrane-bound form of human CPR. All mutants were found capable of reducing cytochrome c yet with different efficiency and their maximal rates of cytochrome c reduction were shifted to lower salt concentration. In particular, residue R246 seems to play a key role in a salt bridge network present at the interface of the hinge and the connecting domain. Interestingly, the effects of mutations, although similar, demonstrated specific differences when present in the soluble or membrane-bound context. Our results demonstrate that the electrostatic and flexibility properties of the hinge segment are critical for electron transfer from CPR to its redox partners.